2021
DOI: 10.3390/math9233045
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Branch-and-Bound Algorithm with OWA Operators in the Case of Consumer Decision Making

Abstract: The ordered weighted averaging (OWA) operator is one of the most used techniques in the operator’s aggregation procedure. This paper proposes a new assignment algorithm by using the OWA operator and different extensions of it in the Branch-and-bound algorithm. The process is based on the use of the ordered weighted average distance operator (OWAD) and the induced OWAD operator (IOWAD). We present it as the Branch-and-bound algorithm with the OWAD operator (BBAOWAD) and the Branch-and-bound algorithm with the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
2
0
1
Order By: Relevance
“…Scientists applied the OWA operator to facilitate decision-making by public managers in sustainable transport [34]. Another study evaluated companies listed on the Lima Stock Exchange considering the level of compliance with the Principles of Good Corporate Governance [32] and in the decision-making of consumers in the city of Barcelona regarding the selection of groceries by neighborhoods that best suit their needs [35]. Finally, the literature review of this article also showed few publications of the OWA operator applied to climate change, evidencing the fifth knowledge gap and an opportunity for academic contribution.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists applied the OWA operator to facilitate decision-making by public managers in sustainable transport [34]. Another study evaluated companies listed on the Lima Stock Exchange considering the level of compliance with the Principles of Good Corporate Governance [32] and in the decision-making of consumers in the city of Barcelona regarding the selection of groceries by neighborhoods that best suit their needs [35]. Finally, the literature review of this article also showed few publications of the OWA operator applied to climate change, evidencing the fifth knowledge gap and an opportunity for academic contribution.…”
Section: Introductionmentioning
confidence: 99%
“…As heuristic algorithms have gained widespread attention, many researchers have adopted swarm intelligence optimization algorithms to find solutions for their models. Among heuristic algorithms, swarm intelligence optimization algorithms, such as Particle Swarm Optimization (PSO), are favored for their simplicity, fast convergence, and ease of implementation compared to precise algorithms (branch and bound [ 13 ], trust region method [ 14 ], etc.) and other heuristic algorithms (genetic algorithm [ 15 ], evolutionary algorithm [ 16 ], etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Los consumidores de productos de belleza han cambiado sus hábitos de consumo y han entrado nuevos compradores a este mercado, generando un gran abanico de oportunidades para dicho sector (Cervellon& Carey, 2011;Lee & Lee 2022). Debido a estos cambios de comportamiento del usuario, el estudio de las decisiones del consumidor y el sector de la belleza se ha convertido en una vertiente de investigación en auge, esto se demuestra con el volumen de artículos y autores que podemos encontrar en las principales bases de datos y con las variables que estas informan (Vizuete-Luciano et al, 2021;Wang et al, 2022). La Web of Science Core Collection reporta un alto número de citas y de artículos publicados en los últimos años, destacando la importancia de este sector y del estudio del consumidor.…”
Section: Introductionunclassified